Avaliação da atividade antinociceptiva e anti-inflamatória de frações das folhas da costus cf. arabicus L. (Costaceae) - Silva , Diego de Farias (2013)
Due to the system does not recognize equations and formulas the resumo and abstract can be found in the PDF file.